Knowledge, Attitude and Practice Regarding Breast Cancer and Breast Self-Examination Among A Sample Of Women In Al-Diwaniyah City - Sarah Abdul Kareem Abdul Jabar; Hassan Raji Jallab (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2024)
Background: breast cancer is the most common cancer among women, also it is the leading cause of cancer-related deaths in low-resource countries. So, every woman should know what it looks like, be aware of any changes, and know what to do if they are discovered. Meanwhile, early diagnosis and management are fundamental steps toward increasing survival and improving the quality of life Aims: The purpose of this study is to determine the knowledge, attitudes and practices of women in Al_Diwaniaya city regarding breast self-examination, and to explore their level of knowledge about breast cancer focusing on some risk factors.Method:  Cross- sectional _ study was conducted among 350 women aged more than 18 years who attended breast screening department in Al- Diwaniyah teaching hospital during the period of study using face-to-face interviews questionnaire. Results: The total sample included in this study was 350 females, regarding the score of knowledge, the results showed near half of participants having moderate knowledge (49.1%), On the other hand, the attitude of study people was more interesting by enrolling questions. Concerning the attitude score, the findings indicated that 64% of the subjects had a moderate attitude. In terms of practice score, the findings revealed that 57% of participants had poor practice and only 6% had good practice. The study discovered that the age groups under 40 had better knowledge, attitudes, and practices than the age groups over 40, with a positive correlation also (p<0.001) in high education group.Conclusions: The results showed most of participants having moderate to good knowledge (78%) moderate attitude but poor practice of breast self-examination. the gap in knowledge in fields of breast self-examination emphasizes on the need to raise awareness among women about the correct method and timing of it.